The effectiveness of self-healing training on job burnout, quality of life, and emotional flexibility in Isfahan\'s social emergency personnel - Zohreh Latifi; Ladan Shafie; Mohammad Soltanizadeh (فصلنامه ابن سینا)
Background and aims: Burnout is one of the most important unavoidable consequences of work stress that causes physical fatigue, changes in job behavior and performance. The purpose of the present study was to investigate the effectiveness of self-healing training on job burnout, quality of life, and emotional resilience of Isfahan's social emergency personnel. Methods: The research method was semi-experimental with pretest/posttest/follow-up design and a control group. The statistical population of the study included all social emergency personnel in Isfahan city. Using the stratified random sampling method, 36 personnel were selected and randomly assigned into two groups (n=18) of experimental and control. The subjects in the experimental group received 14 sessions of 90 minutes of self-healing training. The burnout questionnaire, the WHO quality of life questionnaire, and the emotional flexibility questionnaire were used to collect data in three stages. Analysis of variance with repeated measures was used. Results: Findings showed that self-healing training is effective in reducing burnout, improving quality of life, and emotional resilience of social emergency personnel (p<0.05); So that it affected on all dimensions of burnout, two dimensions of the quality of life (physical and mental health), and all dimensions of emotional flexibility. Conclusion: The self-healing training can be used in stressful work environments to increase tranquility and mental health.